Polygamy in Islamic Law: A Meta-Analysis and Systematic Review - Nafan Torihoran (PT. Ratu Bilqis Azzahira bekerjasama dengan Fakultas Syariah Universitas Islam Zainul Hasan Probolinggo, 2025)
Polygamy remains one of the most debated and controversial practices in Islamic family law, raising significant questions about justice, gender equality, and family welfare in contemporary Muslim societies. This study seeks to answer the central research question: How is polygamy understood and practiced today in light of Islamic legal principles and what are its social and psychological impacts? To address this question, a systematic review and meta-analysis were conducted using the PRISMA framework, analyzing 45 peer-reviewed studies sourced from Scopus, ScienceDirect, PubMed, and other reputable academic databases. The review focused on the legal interpretations of polygamy, its regulation in various Muslim-majority countries (such as Indonesia, Morocco, and Egypt), and its social and psychological consequences for women and children. The findings reveal that while polygamy is religiously permitted as a legal dispensation (rukhshah), it is heavily conditioned on the requirement of justice (as emphasized in Quran 4:3), which is extremely difficult to achieve in practice. Quantitative evidence shows that women in polygamous marriages report significantly lower marital satisfaction and higher levels of depression and anxiety, while children face greater emotional and behavioral challenges compared to those in monogamous families. Moreover, global trends indicate a decline in the acceptance and practice of polygamy, with many legal systems introducing stricter regulations or discouraging it altogether. Despite these insights, research gaps remain, particularly in understanding the long-term effects on children and the perspectives of men in polygamous marriages. Overall, the study underscores that polygamy, as currently practiced, often contradicts the higher objectives (maqasid) of Islamic law aimed at ensuring justice, compassion, and family well-being, suggesting that monogamy better aligns with contemporary ethical and social realities